Balanced mixture of biochar and synthetic fertilizer increases seedling quality of Acacia mangium - Reyes Moreno, Giovanni; Fernandez, María Elena; Darghan Contreras, Enrique (Elsevier, 2021)
Biochar is a charcoal-like substance produced by pyrolisis of organic material from agricultural and forestry wastes, that can improve soil and substrates physical and chemical properties in the field and in plant nurseries. Despite some studies showing the advantages of its use in forestry nurseries, other studies show that biochar effects on seedling growth and quality are variable, and depends on the specific properties of the biochar and the particular species response to it. The objective of this study was to evaluate, through the analysis of the substrate and plant measurements, the effect of biochar produced from Acacia mangium Willd wood residues on the production of the same species seedlings. An experiment with complete factorial design, in a completely randomized arrangement, was established, with 9 treatments resulting from the combination of A. mangium biochar (BAM) and synthetic fertilizer (FS), with 3 dose levels for BAM: 0, 40, and 80 ton • ha−1 and 3 levels for the FS: 0% 50% and 100% of common fertilizer practice in the studied region of Colombia. The quality of the seedlings was estimated using the Dickson index (DQI), which considers the size and biomass allocation of the plant. The addition of BAM + FS increased the cationic exchange capacity, nitrogen, phosphorus, organic matter and carbon in the substrate without modifying the pH or the concentrations of calcium and potassium. Foliar analysis showed an increase in these cations in BAM treatments. An increase of over 130% was found in the DQI of seedlings with BAM + FS, but an intermediate dose of both elements was required to achieve this improvement in seedling quality. Neither of the two fertilizer alternatives alone resulted in good seedling quality.